Electrospun Gelatin/β-TCP Composite Nanofibers Enhance Osteogenic Differentiation of BMSCs and In Vivo Bone Formation by Activating Ca2+-Sensing Receptor Signaling. (1st June 2015) - Zhang, Xuehui; Meng, Song; Huang, Ying; Xu, Mingming; He, Ying; Lin, Hong; Han, Jianmin; Chai, Yuan; Wei, Yan; Deng, Xuliang
Abstract : Calcium phosphate- (CaP-) based composite scaffolds have been used extensively for the bone regeneration in bone tissue engineering. Previously, we developed a biomimetic composite nanofibrous membrane of gelatin/ β -tricalcium phosphate (TCP) and confirmed their biological activity in vitro and bone regeneration in vivo . However, how these composite nanofibers promote the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) is unknown. Here, gelatin/ β -TCP composite nanofibers were fabricated by incorporating 20 wt% β -TCP nanoparticles into electrospun gelatin nanofibers. Electron microscopy showed that the composite β -TCP nanofibers had a nonwoven structure with a porous network and a rough surface. Spectral analyses confirmed the presence and chemical stability of the β -TCP and gelatin components. Compared with pure gelatin nanofibers, gelatin/ β -TCP composite nanofibers caused increased cell attachment, proliferation, alkaline phosphatase activity, and osteogenic gene expression in rat BMSCs. Interestingly, the expression level of the calcium-sensing receptor (CaSR) was significantly higher on the composite nanofibrous scaffolds than on pure gelatin. For rat calvarial critical sized defects, more extensive osteogenesis and neovascularization occurred in the composite scaffolds group compared with the gelatin group. Thus, gelatin/ β -TCP composite scaffolds promote osteogenic differentiation of BMSCs in vitro and bone regeneration in vivo by activating Ca 2+ -sensing receptor signaling.